2006
DOI: 10.1111/j.1365-2265.2006.02507.x
|View full text |Cite
|
Sign up to set email alerts
|

Persisting effects on fasting glucose levels and insulin sensitivity after 6 months of discontinuation of a very low‐dose GH therapy in adults with severe GH deficiency

Abstract: At month 12, the LGH decreased fasting glucose levels and improved insulin sensitivity without altering body composition, whereas the SGH improved body composition without modifying insulin sensitivity. Six months after discontinuation of the LGH treatment (month 18), fasting glucose levels remained decreased and the enhanced insulin sensitivity persisted. In contrast, after discontinuation of SGH treatment (month 18), body composition reverted to baseline without changes in either fasting glucose levels or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
2
11
1
Order By: Relevance
“…Standard dosage was reported to result in persistent impairment [30] or in no change in insulin sensitivity [31]. However, there is no doubt that the metabolic effects of GH are dose-dependent and may be minimized or avoided if an appropriately low replacement dose is used [29,32,33]. In the present study, with the prolonged therapy duration, the insulin sensitivity was decreased in the unmodified rhGH group, but improved the in PEG-rhGH group.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Standard dosage was reported to result in persistent impairment [30] or in no change in insulin sensitivity [31]. However, there is no doubt that the metabolic effects of GH are dose-dependent and may be minimized or avoided if an appropriately low replacement dose is used [29,32,33]. In the present study, with the prolonged therapy duration, the insulin sensitivity was decreased in the unmodified rhGH group, but improved the in PEG-rhGH group.…”
Section: Discussioncontrasting
confidence: 56%
“…In the present study, we not only compared the growth promoting effect of rhGH and PEG-rhGH, but aimed to explore their impact on glucose metabolism and insulin resistance. [30][31][32][33][34][35] according to the animal protocol approved by the Animal Ethical Committee of the China-Japan Friendship Hospital. The rats were housed in regular cages with one rat per cage with free access to water and standard chow unless noted otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…growth hormone doses titrated to normalise serum IGF-1 levels according to sex and age) led to persistent impairment of [7,9] or no change in insulin sensitivity [10,11]. However, investigators using long-term low-dose growth hormone treatment reported gradual but persistent improvement in glucose metabolism in some [12,13], but not all studies [14].…”
Section: Introductionmentioning
confidence: 99%
“…These changes did not persist after 6 months of treatment, possibly as a result of reductions in abdominal visceral fat 7,8 . Other studies have suggested that GH treatment may have no effect or even a beneficial effect on glucose metabolism, especially if used at doses lower than those used in the early RCTs 9–12 . Of concern to clinicians is that the evidence from these studies may not be directly applicable to routine clinical practice, as most RCTs have used stringent eligibility criteria and have been relatively short in duration 13 …”
Section: Introductionmentioning
confidence: 99%